1,4-disubstituted thiosemicarbazide derivatives are potent inhibitors of toxoplasma gondii proliferation - Dzitko, Katarzyna; Paneth, Agata; Plech, Tomasz; Pawełczyk, Jakub; Stączek, Paweł; Stefańska, Joanna; Paneth, Piotr (My University, 2014)
A series of 4-arylthiosemicarbazides substituted at the N1 position with a 5-membered heteroaryl ring was synthesized and evaluated in vitro for T. gondii inhibition proliferation and host cell cytotoxicity. At non-toxic concentrations for the host cells all studied compounds displayed excellent anti-parasitic effects when compared to sulfadiazine, indicating a high selectivity of their anti-T. gondii activity. The differences in bioactivity investigated by DFT calculations suggest that the inhibitory activity of 4-arylthiosemicarbazides towards T. gondii proliferation is connected with the electronic structure of the molecule. Further, these compounds were tested as potential antibacterial agents. No growth-inhibiting effect on any of the test microorganisms was observed for all the compounds, even at high concentrations.
Keywords: thiosemicarbazide derivatives; anti-Toxoplasma gondii activity; antibacterial activity; bacterial topoisomerases; toxicity; docking studies; DFT calculations